2018
DOI: 10.17563/rbav.v37i2.1083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the plasma nitriding conditions on the chemical and morphological characteristics of TiN coatings deposited on silicon

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…This indicates the beginning of the densification and smoothening of the films. The transition from roughening mechanism, due to the limited mobility of surface defects (Stage I) [37] to the smoothing mechanism controlled by the surface diffusion effect (Stage II) [43] is clearly demonstrated by the disappearance of the faceted surface (Fig. 6h).…”
Section: Microstructure and Morphologymentioning
confidence: 95%
See 1 more Smart Citation
“…This indicates the beginning of the densification and smoothening of the films. The transition from roughening mechanism, due to the limited mobility of surface defects (Stage I) [37] to the smoothing mechanism controlled by the surface diffusion effect (Stage II) [43] is clearly demonstrated by the disappearance of the faceted surface (Fig. 6h).…”
Section: Microstructure and Morphologymentioning
confidence: 95%
“…The low-frequency scattering caused by acoustical phonons (TA and LA modes) is related to vibrations of the heavier metal atoms, while optical range scattering (TO and LO) refers to vibrations of the lighter non-metal ions [37]. Furthermore, an increase in the intensity of the optical phonon band suggests the formation of metallic vacancies, while an increase in the intensity of the acoustical band indicates a nitrogen vacancy [38].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…In 2017, Silva et al [71] carried out the titanium nitride synthesis on a glass substrate and reported that the rate of film deposition and film roughness increases with an increase in the thickness of the cathodic cage lid. In 2018, Neto et al [72] grew titanium nitride coating on silicon substrates using numerous gasses composition (1:3 and 3:1 of N 2 − H 2 mixture), processing temperature (300, 350 °C), and processing time (1-4 h). The microstructural images of the sample processed at a low temperature of 300 °C with 1 h processing time revealed that the synthesized coating was not uniform and appears to be uniform with an increase in processing time.…”
Section: Ccpd For Titanium Nitride Synthesismentioning
confidence: 99%